Configurational Path to NPD Project Performance- Involving Source of Innovation in Supply Chain Strategy - Gheshmi, Reza; Zarco, Hugo; Marimon, Frederic (ExcelingTech, 2020)
Abstract— During past twenty years, knowledge integration and product development process, have been considered as two critical strategies for new product development process. The two mentioned strategies were the main focus of industry and also academicians as well as many practitioners). The most significant similarity among the investigations on this integration strategy is the focus on organizations as unit of analysis and in some cases, the investigations was in project level in order to have more accurate and detail results. But in this study we considered project phase and the unit of analysis to be able to take into account the project and different phase’s characteristics. In this way we will be able to find more relevant and practical results for integration different source of knowledge, in different phases of new product development. We analysed 125 new product development projects from total 85 manufacturing firms, which have implemented at least one form of external collaboration among their NPD projects, within 8 different industries in Spain. To make these analysis we used fsQCA method and our finding show that by involving different types of knowledge sources in different phase of NPD projects, the companies may achieved to different level of Cost, Market, Speed and product Novelty performance and these configurations are very between different projects.